Effect of Otago Exercise on Indicators of Sarcopenia in the Elderly - Lee, Soo J.; An, Chang S.; Kim, Jeong L.; Kim, Hae I. (International Journal of Membrane Science and Technology, 2023)
This study was conducted to determine the effect of Otago exercise intervention on muscle mass, muscle strength, and physical performance, which are diagnostic indicators of sarcopenia, in elderly individuals aged 65 or older. The final subjects included 6 individuals in the walking exercise group and 5 people in the Otago exercise group. Walking exercises were conducted 12 times a week for 22 minutes at a time and more than 80 steps per minute whereas the Otago exercise was conducted four times a week for 50 minutes, a total of 12 times under the supervision of a senior movement leader. After the intervention, a diagnostic evaluation of sarcopenia was performed, and before and after the intervention, the intergroup skeletal muscle mass (ASM), grip force (Hand Grip), and SPPB were compared. The three evaluation parameters are related to physical function and showed that after each exercise intervention, the Otago exercise group exhibited an increase in the limb skeletal muscle and the SMI. The walking exercise resulted in a decrease in muscle strength, but the Otago exercise group showed an increase in this metric. The SPPB score increased in the Otago movement group, but no statistically significant results were obtained. It was demonstrated that the Otago exercise positively affects the index of muscle loss in the elderly, and is potentially effective for preventing and managing sarcopenia.